2022
DOI: 10.1007/s11869-022-01272-2
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric micro (nano) plastics: future growing concerns for human health

Abstract: Plastics are an integral but largely inconspicuous part of daily human routines. The present review paper uses cross-disciplinary scientific literature to examine and assess the possible effects of nanoplastics (NPs) concerning microplastics (MPs) on human health and summarizes crucial areas for future research. Although research on the nature and consequences of MPs has seen a substantial rise, only limited studies have concentrated on the atmospheric nanosized polymeric particles. However, due to the intrins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(32 citation statements)
references
References 250 publications
0
32
0
Order By: Relevance
“…45−47 The difference in MPs deposition may result from individual factors. 43,44 Given that some MPs are externalized through exhalation, our findings indicated that the exposure estimation based solely on inhaled air MPs concentrations would overestimate the actual airborne microplastics exposure by 33%, particularly 40% for smaller MPs (<10 μm).…”
Section: ■ Results and Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…45−47 The difference in MPs deposition may result from individual factors. 43,44 Given that some MPs are externalized through exhalation, our findings indicated that the exposure estimation based solely on inhaled air MPs concentrations would overestimate the actual airborne microplastics exposure by 33%, particularly 40% for smaller MPs (<10 μm).…”
Section: ■ Results and Discussionmentioning
confidence: 86%
“…The estimated deposition in the respiratory tract was 526 ± 203 (57–1037) MPs per day. During the period of sample collection, the temperature and humidity were kept moderate and relatively constant, avoiding potential effects on nasal mucociliary clearance. The difference in MPs deposition may result from individual factors. , Given that some MPs are externalized through exhalation, our findings indicated that the exposure estimation based solely on inhaled air MPs concentrations would overestimate the actual airborne microplastics exposure by 33%, particularly 40% for smaller MPs (<10 μm).…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…The size limitations for analyzing plastic fragments are estimated to be 500 μm for visual methods, 20 μm for FTIR, and 10 μm for Raman spectroscopy, respectively. , For thermochemical methods, the traditional size limit for analyzing plastic particles was suggested to be 100 μm to obtain a clear result . However, there have been significant improvements with pyrolysis-GC/MS that can identify and quantify lab-generated and ambient plastic particles with much smaller size. ,, Considering these size constraints, previous studies have focused more on microplastics with sizes ranging from 5 mm to 1 μm. , NPPs have smaller sizes, higher cell affinity, and enhanced surface curvature, making them easier to penetrate into freshwater biological barriers and accumulate in organs than MPPs. Despite their longer atmospheric resident time, enhanced accumulation in the environment, and adverse health effects, nanoplastic particles remain largely uninvestigated due to their small sizes. ,, Hence, it is imperative to identify the chemical composition and mass concentration of nanoplastic particles to accurately assess their potential climate effects and public health risks …”
Section: Introductionmentioning
confidence: 99%